2023
DOI: 10.2478/cjf-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Data on the Distribution of Freshwater Ichthyofauna in Albania

Abstract: In this article, we provide an updated list of freshwater fishes in Albania for each sub-basin. The distribution data and taxa-lists presented are based on a literature review up to October 2022 and intensive fieldwork conducted in the last 15 years. Distributional records of 101 fish species (deriving from 25 families) in 11 different sub-basins are reported. There are new records that include native, alien and translocated fish species. The distinctiveness of Albanian freshwater fishes is highlighted while d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The very recent research and literature data focused to the freshwater of Albania and River Vjosa has confirmed that the current fish fauna consists of 34 species from 10 orders and 14 families (Bianco, 1986;Economidis and Banarescu, 1991;Crivelli et al, 1996;Devillers and Devilers-Terschuren, 1996;Banaresku, 2004;Dudgeon et al, 2006;Dudley et al, 2013;Šanda et al, 2008;Snoj et al, 2009;Markova et al, 2010;Shumka et al, 2023) Chelon ramada, Chelon salienes, and Chelon labrosus), Seabream (Sparus aurata), Seabass (Dincentrarchus labrax), Flatfish (Platichthys flesus, common sole (Solea spp. ), etc., while the resident species associated with saline water are numerically prevalent with the two species Atherina boyeri and Aphanius fasciatus showing presence and significance.…”
Section: Fish Species River Vjosamentioning
confidence: 89%
See 1 more Smart Citation
“…The very recent research and literature data focused to the freshwater of Albania and River Vjosa has confirmed that the current fish fauna consists of 34 species from 10 orders and 14 families (Bianco, 1986;Economidis and Banarescu, 1991;Crivelli et al, 1996;Devillers and Devilers-Terschuren, 1996;Banaresku, 2004;Dudgeon et al, 2006;Dudley et al, 2013;Šanda et al, 2008;Snoj et al, 2009;Markova et al, 2010;Shumka et al, 2023) Chelon ramada, Chelon salienes, and Chelon labrosus), Seabream (Sparus aurata), Seabass (Dincentrarchus labrax), Flatfish (Platichthys flesus, common sole (Solea spp. ), etc., while the resident species associated with saline water are numerically prevalent with the two species Atherina boyeri and Aphanius fasciatus showing presence and significance.…”
Section: Fish Species River Vjosamentioning
confidence: 89%
“…The alien fish that has been introduced here from a number of continents, originating from various biogeographic areas has also reached Vjosa basin (Smith and Darwal, 2006;Oikonomou et al, 2014;Leonardos and Sinis, 1998;Stierandová et al, 2016;Shumka et al, 2018a;Shumka et al, 2018b;Shumka, 2019;Meulenbroek et al, 2018;Shumka et al, 2020a;Shumka et al, 2020b;Shumka et al, 2020c;Meulenbroek et al, 2020;Pietrock et al, 2022;Shumka et al, 2023a;Shumka et al, 2023b). These species have a broader range of ecological tolerances and occupy a spectrum of ecological niches (Pseudorasbora parva, Gambusia holbrooki, Carassius gibelio, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Geographic coverage and lakes surface data analysed: The rivers of Albania are included in the 420-Southeast Adriatic Drainage on the worldwide ecoregion map [25,26]. To the best of our knowledge, the distribution and species composition of freshwater fish species serve as the basis for this map of freshwater ecoregions, which also includes important ecological and evolutionary features [27]. Albania is home to multiple major, currently autonomous river and lake systems (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although the Prespa Lakes do not have a surface outflow of water, there are subterranean connections with Lake Ohrid (Amataj et al, 2007). The Danube basin includes only a very minor portion of the Albanian Alps in the country's northernmost region [27]. All Albanian rivers have extremely varying seasonal discharges; in certain cases, summer discharges might be more than ten times lower than winter discharges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation